Trade and Transport Corridor Management Toolkit - Kunaka, Charles (World Bank, 2015)
Global trade moves along a few select high-density routes or corridors. Such routes have existed for several millennia, of which the Silk Road is the most famous. In fact, all regions of the world, developed and developing, have several trade and transport corridor initiatives.